Politics of Space in The Context of The Right to the City and Gender: The Case of KYK Residences in Erzincan - Suat Tuysuz; Melek Eryentü Gürel; Recep Gülmez (Journal of Economy Culture and Society)
In Turkey “termination of a mixed university student residence” policy was put into practice by the Ministry of Youth and Sports in 2013. This policy has created an actual situation that proposes the placement of male students in the residences that are close to the center, and the female students in the student residences in locations that can be considered deserted and remote for women in Erzincan. The sample of this study is composed of 459 people, including both male and female students, who live in all Higher Education Student Loan and Housing Board (HESLHB) residences in the city. The surveys conducted on the sample form the data of the research. The data were analyzed with independent sample t-test and ANOVA test. The findings show that the policy on the termination of mixed residences, which may be referred to as the gendering of space, creates gender inequity. The results of the study show that the visibility of female students in public-urban areas has been limited in line with conservative and patriarchal policies which delimits their right to the city. However, it shows that this results in the fact that male students are pushed into a more financially disadvantaged position.